The effects of body mass index and motor skills on physical fitness through students’ intrinsic motivation - Ikhsan Ika Putra; Kamal Firdaus; Masrun Masrun; Liza Liza (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to examine the direct and indirect effects of body mass index (BMI) and motor skills on physical fitness through intrinsic motivation among upper-grade elementary school students. This research employed a quantitative causal-associative design using path analysis. A total of 59 students from grades IV–VI at SDN 05 Jaruai were selected using proportionate stratified random sampling. Physical fitness was measured using the Indonesian Student Fitness Test (TKSI), motor skills were assessed through the Motor Ability Test, BMI was calculated using anthropometric measurements, and intrinsic motivation was measured using the Intrinsic Motivation Inventory (IMI). Data were analyzed using descriptive statistics, assumption testing, and path analysis with Jamovi 2.6.44. The results indicated that motor skills significantly affected intrinsic motivation (β = 0.303, p = 0.017) and physical fitness (β = 0.229, p = 0.011), while intrinsic motivation showed the strongest effect on physical fitness (β = 0.661, p < 0.001). Conversely, BMI demonstrated no significant direct or indirect effects. These findings highlight the important role of intrinsic motivation in strengthening the relationship between motor skills and physical fitness.